Texture mapping of warp knitted shoe upper based on ARAP parameterization method - Guilong Cheng; Aijun Zhang; Yanting Zhang (AUTEX Research Journal)
In order to realize the design of the warp knitted upper based on the three-dimensional shoe model, this study investigates the texture mapping technique based on angle-preserving and area-regularizing as-rigid-as-possible (ARAP) parameterization. The ARAP algorithm, based on both partial and global considerations, is utilized to parameterize the 3D mesh. Moreover, detailed methods for calculating 3D vertex adjustments and selecting seam lines during the unfolding process are provided. Additionally, discrete harmonic and parametric optimization unfolding algorithms are employed to enhance texture mapping quality. To reduce mesh distortion, the results of discrete harmonic parameterization are used as inputs for ARAP parameterization, making the mapping effect more natural and reducing the number of required optimizations. Experimental results demonstrate that the proposed method maintains a balanced distribution of angles and areas while minimizing conformal distortions, thereby achieving superior texture mapping.